Oxidation and/or reduction of manganese species by γ-ray and He2+ particle irradiation in highly concentrated carbonate media. (February 2016) - Ghalei, Mohammad; Vandenborre, Johan; Blain, Guillaume; Haddad, Ferid; Mostafavi, Mehran; Fattahi, Massoud.
Abstract: The aim of this study is using He 2+ ( E =64.5 MeV) and γ radiolysis for initiating and controlling the oxidation/reduction mechanism of Mn in highly concentrated carbonate media (5 mol l −1 ). For obtaining the best experimental conditions, electrochemistry was performed firstly. Radiolysis was performed; first, reduction of Mn(VII) and second, oxidation of Mn(II), each part was performed under He 2+ and γ-ray irradiation. Gγ(–Mn(VII))=1.07×10 −7  mol J −1 and GHe2+ (–Mn(VII))=3×10 −8  mol J −1 that shows higher efficiency for γ radiolysis with dose rate 1000 times less than α one. Gγ(–Mn(VII))/GHe2+ (–Mn(VII))=5.6 and Gγ(H2 )/GHe2+ (H2 )=0.5 confirm radical mechanism for radio-oxidation/reduction. Heterogeneity of irradiation plays an important role on hydrolysis. Final product oxidation state was determined by XPS and SEM for Mn solid precipitated after the reduction and oxidation experiments. Highlights: Mn oxidation/reduction in 5 M carbonate solutions under He 2+ /γ were investigated. Speciation of Mn under irradiation was performed by in situ UV spectroscopy. Mn reduction is induced by the radical species from the solution radiolysis. Mn reduction mechanism under irradiation is: Mn(VII)→Mn(V)→Mn(IV). Mn oxidation mechanism under irradiation is: Mn(II)→Mn(III)→Mn(IV).